Relationship between vitamin D and osteoarthritis - Natalia G. Kashevarova; Liudmila I. Alekseeva; Elena A. Taskina; Ekaterina A. Strebkova; Evgenia P. Sharapova; Natalya M. Savushkina; Kirill M. Mikhaylov; Svetlana I. Glukhova; Olga G. Alekseeva; Danil M. Kudinsky; Nikolay V. Demin; Elena Yu. Samarkina; et al. (Терапевтический архив, 2025)
Background. Osteoarthritis (OA) is a common joint disease and one of the leading causes of disability worldwide. The role of vitamin D in the etiology and development of OA is still unclear, but it may be important for both diagnosis and timely therapy.